Review of Pierluigi Pellini, Tre grandi critici. Luigi Blasucci, Remo Ceserani, Francesco Orlando (Siké, 2023) (ENTHYMEMA, 2025)
Review of Pierliugi Pellini, Tre grandi critici. Luigi Blasucci, Remo Ceserani, Francesco Orlando. Siké, 2023.
Keywords: Comparative Literature; History of Criticism; Literary Theory